2011
DOI: 10.1007/s11426-011-4357-0
|View full text |Cite
|
Sign up to set email alerts
|

The intensification of luminol electrochemiluminescence by metallic oxide nanoparticles

Abstract: In this work, the intensification of luminol electrochemiluminescence (ECL) by metallic oxide nanoparticles (MONPs), as ZnO, MnO 2 , In 2 O 3 and TiO 2 , under alkaline condition is reported and the related mechanism is studied. It is found that all four types of those MONPs exhibit the effect toward the ECL intensification of luminol. Furthermore, the silica sol-gel film is taken to immobilize the MONPs onto the platinum electrodes. The so-obtained modified electrodes also show the enhanced ECL and better sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Owing to possessing the property of mimic peroxidase activity, the Fe 3 O 4 nanospheres can catalyze the electrooxidation of H 2 O 2 , which will lead to the amplification of the ECL signal intensity of luminol-H 2 O 2 system. Meanwhile, TiO 2 has been reported to accelerate electron transfer by Song et al [40], and enhance the ECL signal of luminol reported by Tu's group [23][24][25]. Table 1, the resulted LOD in this work is lower than that using other analytical methods [8,10,42,2].…”
Section: Comparison Of Different Ecl Responsesmentioning
confidence: 60%
See 1 more Smart Citation
“…Owing to possessing the property of mimic peroxidase activity, the Fe 3 O 4 nanospheres can catalyze the electrooxidation of H 2 O 2 , which will lead to the amplification of the ECL signal intensity of luminol-H 2 O 2 system. Meanwhile, TiO 2 has been reported to accelerate electron transfer by Song et al [40], and enhance the ECL signal of luminol reported by Tu's group [23][24][25]. Table 1, the resulted LOD in this work is lower than that using other analytical methods [8,10,42,2].…”
Section: Comparison Of Different Ecl Responsesmentioning
confidence: 60%
“…Similarly, titanium dioxide nanoparticles (TiO 2 ) have also become an attractive nanomaterial for immobilizing biomolecules on electrode surface owing to its inherent great biocompatibility, photocatalytic capability, high specific surface area, electrotransfer conductivity and chemical inertness [22]. Besides, Tu's group has demonstrated that TiO 2 can enhance the ECL of luminol and the enhancement is directly related to ROS [23][24][25]. GR, a two-dimensional construction material of sp 2 conjugated carbon atoms [26], is emerging as a rising star in the field of material science due to its extraordinary intrinsic properties [27,28] and structural features [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Here the comparison on performance of TiNTs with TNHSs is listed in Table 1b, the response toward H 2 O 2 on TiNTs functionalized ITO is greater. Even compared with those titania-based nano-composites, the present work had equally analytical merit (see Table 1c), although there was some datum obtained from the static mode (14,43), which was in native superiority than dynamic mode.…”
Section: Optimisation Of the Ecl Performance Of Luminol In This Ecl-fmentioning
confidence: 72%
“…The subsequent chemical reaction between the oxidized luminol and H 2 O 2 (or O 2 ) produces ECL signal. Since the first report on the observation of ECL response for luminol at the electrode surface in alkaline solution [10], numerous attempts have been done to find effective approaches for the enhancement of ECL signal intensity of luminol in neutral medium [11][12][13][14]. It has been shown that the ECL reaction of luminol with oxygen or hydrogen peroxide is more efficient in alkaline medium through modification of the electrode surface with nano-materials [12,15].…”
mentioning
confidence: 99%
“…Since the first report on the observation of ECL response for luminol at the electrode surface in alkaline solution [10], numerous attempts have been done to find effective approaches for the enhancement of ECL signal intensity of luminol in neutral medium [11][12][13][14]. It has been shown that the ECL reaction of luminol with oxygen or hydrogen peroxide is more efficient in alkaline medium through modification of the electrode surface with nano-materials [12,15].With the development of nanotechnology, various types of nano-structured materials with outstanding properties are being synthesized and applied for the construction of novel sensors and biosensors. Nano-structured materials provide higher effective surface area and higher catalytic activity in comparison with their respective bulk materials.…”
mentioning
confidence: 99%